Evaluating Preferences of Hospitalized Diabetes Patients for Hospital-Wide Glycemic Control Programme: A Discrete Choice Experiment - Jing Dai; Ting He; Xiaodie He; Huaying Li; Lintong Li; Jie Sun; Jie Pan; Cheng Ji (Journal of Diabetes Research)
Conclusion: Treatment preferences of hospitalized diabetes patients are mainly influenced by antihyperglycemic effectiveness, adverse reactions, healthcare providers, and individual characteristics. Comprehensive consideration and an individualized therapy strategy should be given when constructing a hospital-wide glycemic control programme.